Gender-Ambiguous Voice Agents for Mitigating Gender Bias in Voice User Interfaces in the Context of Autonomous Driving (Estudos em Design, 2025)
Lately, Voice User Interfaces (VUIs) have been widely applied in smart devices. However, the current design of the voice agents used by these systems have resulted in harmful gender bias during this human-computer interaction. To reduce this bias, gender ambiguous voice agents have been considered as a potential solution. This exploratory study aims to investigate the effects of user gender and the application of gender ambiguous voice agents in VUIs. An online experiment (N=50) investigates the perception of four usability factors in the context of multiple automated driving scenarios. Users are presented with two types of gender ambiguous voice agents and two types of wording for each message to evaluate each scenario. Our findings reveal that using gender ambiguous voice agents in VUIs significantly closes the gap in scores between user genders and that the user’s gender has no significant effect on the perception of usability factors.
Keywords: User Experience Design; User Interface Design; Voice User Interfaces; Voice Agents; Gender Ambiguous Voice